Analysis of the Empowerment Level of Rice Paddy Farmers in Abenggi Vilage Landono Distric, South Konawe Regency - Jusman, Jusman; Sidu, Dasmin; Hidrawati, Hidrawati (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
Empowerment is a structured and planned process to increase the ability and independence of farmers in farm management. The study aims to analyze the program forms and the empowerment levels of lowland rice farmers. The research was conducted from April to December 2020 in Abenggi Village, Landono District, South Konawe Regency, Southeast Sulawesi. The location determination is done purposively, considering that the majority of the people work as farmers. The research population was 280 household lowland rice farmers, and the sample was 15% of the total members of the farmer population of 42 respondents. The data were analyzed qualitatively and quantitatively. Qualitatively analyze to explain the form of empowerment with research variables, including types of empowerment assistance. Quantitatively is used to determine the level of empowerment of lowland rice farmers by using variables to show economic and social empowerment, including the story of ability and independence of farmers in managing potential, planning and solving problems in the future, self-direction, and bargaining power. The results showed that the empowerment program for lowland rice farmers consists of capital assistance through the PUAP program, provision of infrastructures such as irrigation facilities, farm roads, and grain drying places. The lowland rice farmers are empowered on the economic aspect, but not yet on the social part.